EDUKASI MAKANAN SEHAT PUJAAN HATI GUNA MENINGKATKAN STATUS GIZI DI PUSKESMAS GUNUNG ANYAR SURABAYA: EDUKASI MAKANAN SEHAT PUJAAN HATI GUNA MENINGKATKAN STATUS GIZI DI PUSKESMAS GUNUNG ANYAR SURABAYA - Wahyuni Dyah Parmasari; Sukma Sahadewa; Devi Dwi Rianti, Emilia (JCS, 2024)
Development will develop based on quality resources, so it must have humans with good nutritional status and in essence it starts from when they are still in the womb. Nutrition is one of the things that affects human health, where ideal nutrition is related to the development of intelligence, health, skills and supports normal child growth according to their age. The aim is to further socialize and provide insight through healthy food education "Pujaan Hati" in order to improve nutritional status. The community service method provides education in the form of counseling and demonstrating how to make anti-stunting jelly pudding. The results of the education are known that the condition of stunting is 12 toddlers, pre-stunting 3 toddlers, 30 babies prone to stunting, and 11 KEK pregnant women. The conclusion is the need for balanced nutrition for the body, with healthy foods that have an impact on physical health and intelligence. Providing moringa leaves in the form of anti-stunting jelly pudding (pujaan hati) will meet the needs of vitamins and nutrients.